PENGUKURAN METODE RASIO INFORMASI, RASIO SORTINO DAN ROY SAFETY FIRST RATIO PADA KINERJA REKSADANA SAHAM SYARIAH PERIODE 2015-2017 - Nur Rohman Azis; Atina Shofawati (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
The Objective of this research is to identify whether there is a different level performance of mutual funds in syariah shares among Information Ratio, Sortino Ratio, and Roy Safety First Ratio. This analysis using qualitative descriptive. In this case, the authority of money service website mentions there are 21 mutual funds in syariah shares could be taken as the sample of the analysis by using purposive sampling method. Verification result is done by One-way Anova test. The measurement result of the mutual fund in syariah shares uses the method Information Ratio provides 3 mutual funds in syariah shares are in positive performance in 2015 and 2017 and 5 mutual funds in syariah shares are in negative performance in 2016. It means there is a different performance result of mutual fund in syariah shares. The result Sortino ratio provides all of mutual fund share are in negative performance in all of year. It means there is no different performance result of mutual fund in syariah shares. The result Roy Safety First Ratio provides all of mutual funds in syariah shares are in negative performance in 2015, 2 mutual funds in syariah shares are in negative performance in 2016 and 4 mutual funds in syariah shares are in positive performance in 2017. It means there is no different performance result of mutual fund in syariah shares.Keywords: Performace of mutual funds, Information Ratio, Sortino Ratio, Roy Safety First Ratio, Mutual Funds in Syariah SharesREFFERENCESAhmadinia, hamed. 2012. Evaluation performance Of 50 Top Companies Listed In Tehran stock Exchange By Sortino, erov And M3. International journal of economics And Finance. Vol. 4, No. 1; Januari 2012Anoraga, Panji dan Panji Pakarti. 2001. Pengantar Pasar Modal. Edisi Revisi. Jakarta: PT Rineka Cipta.Halim, Abdul. 2005. Analisis Investasi. Edisi II. Jakarta: Salemba EmpatHartono, Jogiyanto. 2007. Teori Portofolio dan Analisis Investasi Edisi 2007. Yogyakarta. BPFE.Rudiyanto. 2013. Sukses Finansial Dengan Reksadana. jakarta: Elex Media Komputindo.Hartono, Jogiyanto, 1998, Teori Portofolio dan Analisis Investasi. Edisi pertama. BPFE.YogyakartaSimforianus, Hutagaol, Tanthu. 2008. Analisis Kinerja Reksadana Saham Dengan Metode Raw Return, Sharpe, Treynor, dan Sortino. Journal of Applied Finance And Acounting Vol. 1 No.1 November 2008: 193-226Tandelilin, Eduardus. 2010. Portofolio dan Investasi Teori dan Aplikasi. Yogyakarta. BPFEWidjaja, Gunawan dan Almira Prajna Ramaniya. 2006. Reksa Dana dan Peran Serta Tanggung Jawab Manajer Investasi dalam Pasar Modal. Jakarta:Kencana Prenada Media Group.